A Chinese Patient with Spastic Paraplegia Type 4 with a De Novo Mutation in the SPAST Gene - Li Xu; Zijuan Peng; Chunhui Zhou; Jiqing Wang; Hunjin Luo; Qin Lu; Zhengjun Bao (Case Reports in Genetics)
Background. Spastic paraplegia type 4 (SPG4) is the most common type of hereditary spastic paraplegia (HSP) caused by mutations in the SPAST gene. Case Presentation. We report the case of a 27-year-old pregnant Chinese woman with HSP in whom we identified a missense mutation in the SPAST gene (c.1496G>A, p.Arg499His) and a nonsense mutation in the NEFH gene (c.289G>T, p.Glu97∗) via whole-exome sequencing; this finding corroborated that of Sanger sequencing. The patient exhibited the pure SPG4 phenotype with onset during childhood. The SPAST mutation was absent in the parents and paternal relatives. However, the NEFH mutation was identified in five people with no clinical phenotype. Based on theoretical conjecture and the family gene segregation information, we concluded that the SPAST mutation, but not the NEFH mutation, accounted for the proband’s phenotype. Eventually, the woman gave birth to a healthy baby girl with the NEFH mutation. Conclusion. In this report, we identified a missense mutation in the SPAST gene (p.Arg499His) in a 27-year-old pregnant Chinese woman with HSP. We believe that this study expands the knowledge about the clinical parameters and mutation spectrum of SPG4.